Telomeric and interstitial telomeric sequences in holokinetic chromosomes of Lepidoptera: telomeric DNA mediates association between postpachytene bivalents in achiasmatic meiosis of females - Rego, Alena; Marec, Frantisek (Chromosome research, 2003)
Telomeres, besides their main role in the protection and maintenance of chromosome ends, have several other vital functions in the cell cycle. We studied their role in the achiasmatic meiosis of female Lepidoptera, insects with holokinetic chromosomes. By fluorescence in-situ hybridization (FISH) with the insect telomeric probe, (TTAGG)n, we mapped the distribution of telomeric and interstitial telomeric sequences (ITS) in female meiotic chromosomes of two species, Orgyia antiqua with a reduced chromosome number (2n = 28) and Ephestia kuehniella mutants, possessing a radiation-induced chromosome fusion in the genome (2n = 59). In addition to the strong typical telomeric signals, O. antiqua displayed weaker hybridization signals in interstitial sites of pachytene bivalents. The observed ITS most probably reflect remnants of chromosomal rearrangements and support the hypothesis that the Orgyia karyotype had arisen by multiple fusions of ancestral chromosomes. On the other hand, the absence of ITS in the chromosome fusion of Ephestia indicated the loss of telomeres before the two original chromosomes fused. When the telomeric probe was amplified by enzymatic reaction with tyramid, the number of ITS observed increased in Orgyia, and a few ITS were also observed in several chromosomes of Ephestia but not in the fused chromosome. This suggests that the genomes of both species also contain ITS other than those originating from chromosome fusions. The analysis of female meiotic prophase I revealed non-homologous associations of postpachytene bivalents mediated by telomeric DNA, which were not observed in the pachytene stage. Surprisingly, in early postpachytene nuclei the telomeric associations also involved ITS, whereas later postpachytene nuclei displayed chains of bivalents interconnected only by true telomeres. This finding favours a hypothesis that telomeric associations between bivalents play a role in chromosome segregation in the achiasmatic meiosis of female Lepidoptera.
Keywords: Image Processing, Computer-Assisted; telomery; buněčné jádro; karyotypizace; Cell Nucleus; Telomere; ženské pohlaví; zvířata; Meiosis; meióza; Lepidoptera; Female; hybridizace in situ fluorescenční; Karyotyping; DNA; In Situ Hybridization, Fluorescence; počítačové zpracování obrazu; Animals